Experiences of Mental Health Nurse’s Caring for Schizophrenic Patients with Aggressive Behavioral Disorders: Phenomenology Study - Syamsudin, Achmad; Yusuf, Ah; Aditya, Ronal Surya; Fitriasari, Andikawati (International Journal of Psychosocial Rehabilitation, 2020)
Aggressive behavior hurts health as well as the safety of patients and mental hospital staff. almost all nurses and other health professionals have experienced aggressive patient behavior both verbally and physically. Aggressive attacks by patients on hospital staff are a rare but unavoidable phenomenon. This might happen at any time especially for nurses who are near the patient to provide nursing care. Objective To explore nurses 'experiences in dealing with patients' aggressive behavior. Qualitative research with a phenomenological approach. the number of participants in this study was 12 nurses. Selection of participants through a purposive sampling method with inclusion criteria: 1) Minimum nurse D-III nursing education, work experience more than 3 years 2) Communicate verbally well. Data analysis used the Thematic theory of Colaizzi. Results: 4 themes were obtained, namely: Experience in providing nursing care, Aggressive behavioral intervention, Needs Nurse wants, Competencies of mental health nurses. And found 10 sub-themes. Nurses need more attention because they are the front line in mental health hospital services. The attention is in the form of providing facilities in the form of regulations, training, etc. Hospitals need to develop a standard for aggressive behavior management that is systematic and practical. Provide education, debriefing, and a work environment as well as adequate equipment for nurses to increase the effectiveness of preventive measures and the handling of aggressive patient behavior.